Treatment adherence in hypertension and diabetes mellitus: an integrative review - Aline Moraes de Abreu; Níkolas Paim Brandão; Sonara Lúcia Estima; Michelli Cristina Silva de Assis (Universidade Federal de Santa Maria, 2016)
Aim: to analyze the scientific literature on the main causes of adherence or not to the treatment of hypertension and type 2 diabetes mellitus. Method: an integrative literature review, which selected full articles published between 2005 and 2015, detected by the descriptors "medication adherence", "patient compliance"," type 2 diabetes mellitus", "hypertension" and "nursing". The searches were conducted in the Virtual Health Library (Nursing), LILACS and PubMed databases. Results: Twenty-six articles were selected, the factors associated with adherence were: young age, to have a healthy lifestyle and items related to therapy. On the other hand, among the factors that lead to poor adherence, there are lower income, little knowledge about the disease and complex treatment. Conclusions: the adherence factors to the treatment of hypertension and diabetes are related to the patient, to the type of treatment and health system, which constitute important issues to be approached by nurses